Identification of Japanese Astraeus, based on morphological and phylogenetic analyses - Fangfuk W. (2014)
To clarify the diversity of Astraeus in Japan, 35 collections of Astraeus basidiomata from Japan and Thailand were examined for their morphological characteristics and the nucleotide sequences of the rDNA ITS region and compared with several worldwide Astraeus species. Japanese Astraeus specimens were separated into two groups based on basidiome size, shape of exoperidium, and ornamentation and size of basidiospores. The phylogenetic tree analyses supported the separation, and the morphological groups belonged to different clades. The Japanese Astraeus group 1, morphologically matched to Astraeus hygromerticus var. koreanus, showed the closest phylogenetic relationship with Astraeus hygrometricus from North American and Mediterranean regions, suggesting that the Astraeus group 1 can be indentified as A. hygrometricus var. koreanus. Another Astraeus group, group 2, morphologically matched to A. hygrometricus s. l., showed a distinct monophyletic clade that was separated from A. hygrometricus complexes, indicating an undescribed species. © 2010 The Mycological Society of Japan and Springer.